DEVELOPMENT OF COORDINATION ABILITIES AND BALANCE IN CHILDREN OF MIDDLE SCHOOL AGE - Mirzaboev Khurshedjon Rustamovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article presents the various approaches to the definition of the terms equilibrium, balance, stability, and metastability, giving the characteristics of their types. It describes the conditions of the balance preservation and the equilibrium-providing system of the person. It shows the basic principles of the development of the equilibrium function, which is important for effective training. It considers the general requirements for the development of balance function and exercise for the formation of this ability.